Application of obesity treatment algorithims to Canadian adults - Mason, C; Katzmarzyk, P.T (European journal of clinical nutrition, 2005)
Objective: The purpose of this study was to apply obesity treatment algorithms to a representative sample of Canadians to determine their potential impact on the population. Design: The Canadian Heart Health Surveys (1986-1992) were used to describe the prevalence of adults (18-64 y) that would be eligible for weight loss treatment according to the US NIH algorithm, which uses body mass index (BMI), waist circumference (WC), and the presence of two or more cardiovascular disease (CVD) risk factors. Similar algorithms based on CVD risk factors and a single measure of either BMI or WC alone were also evaluated. Results: Using the NIH algorithm, 24% of Canadians (28% men, 19% women) would be identified for weight loss treatment. Virtually, all subjects received the same treatment recommendations when using BMI and CVD risk factors only, while 22% (23% men, 21% women) would meet the criteria for treatment using WC and CVD risk factors only. Conclusions: Approximately one in four Canadians would be eligible for weight loss treatment using the NIH obesity treatment algorithm. However, the algorithm may be improved through the incorporation of more sensitive WC thresholds.